Natural water cycle simulation / Amin Abd. Razak - Amin, Abd. Razak (2004)
The name of this project is Natural Water Cycle Simulation (NWCS).This system consists of two subsystem, the interface for this system and the simulation. Interface function as an introductory page and provides navigation buttons that will guide user to interact with it.This simulation is showing the process that involved in natural water cycle phenomena in 3D visualization.The internet had become an important medium of communication today. Since then, the world had seen the evolution of information representations. The use of 3D on the Web allows virtually infinite amount of interactivity. The most important achievement of 3D technology is the making of 3D simulation, which provides interaction with the user in 3D graphic that look exactly like real. The Natural Water Cycle Simulations applies the concept of simulation by creating 3D objects like object in the real world. It emphasizes on the user interactivity where user can interact with the simulation and learn through 3D environment. The Natural Water Cycle Simulation concerns the use of simulations as a mean of learning something and shows to the user what they can see in a real world. Creating a 3D graphics of the environment in natural water cycle process. In another word, a realistic-looking process is presented on the computer screen. This report provides an overview of the project development. It is also contains the introductions to the conception of the project, the scope and boundaries covered by the simulation, the phases of the system analysis and development processes and the system design.